2015
DOI: 10.1017/s0954579415001224
|View full text |Cite
|
Sign up to set email alerts
|

Role of temperament in early adolescent pure and co-occurring internalizing and externalizing problems using a bifactor model: Moderation by parenting and gender

Abstract: We contribute to the literature on the relations of temperament to externalizing and internalizing problems by considering parental emotional expressivity and child gender as moderators of such relations and examining prediction of pure and co-occurring problem behaviors during early to middle adolescence using bifactor models (which provide unique and continuous factors for pure and co-occurring internalizing and externalizing problems). Parents and teachers reported on children’s (4.5- to 8-year-olds; N = 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 85 publications
4
34
1
Order By: Relevance
“…Adolescents vary on a wide variety of dimensions that include temperament 40 , sensitivity to parenting 41 , biological vulnerabilities 42, 43 , psychopathology 44, 45 , personality 46 and relationship history 4748 . These individual differences between adolescents may moderate the association between parenting practices and adolescent outcomes and further refine the meaning of sensitive attunement to encompass the ways in which parents adapt their practices to the characteristics of a particular adolescent.…”
Section: Challenges To Implementing Parenting Practicesmentioning
confidence: 99%
“…Adolescents vary on a wide variety of dimensions that include temperament 40 , sensitivity to parenting 41 , biological vulnerabilities 42, 43 , psychopathology 44, 45 , personality 46 and relationship history 4748 . These individual differences between adolescents may moderate the association between parenting practices and adolescent outcomes and further refine the meaning of sensitive attunement to encompass the ways in which parents adapt their practices to the characteristics of a particular adolescent.…”
Section: Challenges To Implementing Parenting Practicesmentioning
confidence: 99%
“…Further, some work indicates that positive parenting practices are more closely associated with some adjustment domains more than others. Specifically, parenting expressivity during childhood was more strongly associated with lower externalizing behaviors during adolescence than internalizing symptoms or the co-occurrence of externalizing and internalizing problems (Wang et al 2016). Similarly, parental monitoring was found to be associated with substance use in a sample of predominantly white adolescents only when internalizing symptoms were low (Villarreal and Nelson 2018).…”
Section: Parenting and Adolescent Adjustmentmentioning
confidence: 88%
“…Previous research has demonstrated the co-occurrence of internalizing symptoms, externalizing behaviors, and substance use (Chan et al 2008). Parenting practices, including culturally embedded parenting practices, have been linked to adolescent adjustment (Caughy et al 2011;Wang et al 2016). Further, parenting styles have been linked to positive youth adjustment and lower levels of maladjustment among adolescents (Bámaca-Colbert et al 2018;Carlo et al 2018;Pinquart 2017aPinquart , 2017b.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of foreign and domestic literature has shown that currently relevant is the study of the factors that determine a person's temperament, the connection of temperament with the occurrence and development of diseases of the cardiovascular system, as well as the interdependence of temperament and human behavioral features. However, there is a need to expand ideas about the role of biologically determined properties of temperament in the personal design of protective behavior, about the role and place of psychological protection in the overall structure of individuality (Abdoli Dehnavi, et al 2016;Wang, et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In general, we can state the lack of integration of theoretical and empirical data into a single concept. Therefore, the problem of personality defense mechanisms with different dominance of the type of temperament can be considered as one of the most urgent in the psychology of personality, based on real practical inquiry (Wang, et al 2016;Di Giuseppe, et al 2019).…”
Section: Introductionmentioning
confidence: 99%